HUBUNGAN KESIAPAN BELAJAR MANDIRI TERHADAP KEMAMPUAN ACTIVE LEARNING DAN CRITICAL THINKING MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Amalia Nurlita,; Agneta Irmarahayu,; Sri Wahyuningsih, (2021)
The curriculum with a problem-based learning (PBL) approach in accordance with SPICES learning strategy has been implemented by the Indonesian Medical Council. The medical school, University of Pembangunan Nasional Veteran Jakarta (FK UPNVJ) has been implementing the PBL learning method since 2006/2007. Active learning and critical thinking abilities are the two main components that students must have in learning with SPICES strategy. The research aims to describe the self-directed learning readiness, the ability of active learning and critical thinking, and the relationship between both of them. An analytical observational study with a cross-sectional design was selected for this research. The reasearchers used an undergraduate female preclinical medical students of the last year education (2017) as a participant. Self-Directed Learning Readiness Scale (SDLRS) and Self Assessment Scale on Active Learning and Critical Thinking (SSACT) are used to asses self-directed learning readiness and ability of critical thinking and active learning. 60 students (65.9%) had high self- directed learning readiness and 87 students (95.6%) had ambivalent active learning and critical thinking skills. There was no relationship between self- directed learning readiness towards the ability of active learning and critical thinking (p=0.548) from Fisher's Exact test result. Student psychology and the number of participants in the class need to be considered so that students can apply learning methods during college for lifelong learning.